DAMPAK SERVICE QUALITY, DIGITAL MARKETING DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PADA GERAI HANDPHONE DI KOTA PALOPO - Fitriyani Fitriyani; Edi Maszudi; Muhammad Ikbal (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to determine the impact of service quality, digital marketing and brand trust on purchasing decisions. Type of quantitative research. The types of data used are primary, secondary and per se. The method used is to distribute questionnaires to respondents. The collected data will be analyzed using SPSS 29 to determine how much influence the independent variables (service quality, digital marketing and brand trust) have on the dependent variable (purchase decisions). The analysis used is the reliability test, validity test, t test and f test. This study partially shows that service quality has a positive and significant influence on purchasing decisions. The results of this study partially show that digital marketing has a positive and significant influence on purchasing decisions. The results of this study partially show that brand trust has a positive and significant influence on purchasing decisions. Service quality, digital marketing and brand trust have a positive and significant influence on purchasing decisions at cellphone outlets in Palopo City. This study was conducted from September to November 2024.